A Binocular Information Source for Size Perception - Kim, Nam-Gyoon (Frontiers in Psychology, 2017)
For too long, size perception research has been guided by the size distance invariance hypothesis (SDIH). Although research to validate this hypothesis has been largely inconclusive, the hypothesis has endured, perhaps in part because alternative information sources for size perception were lacking. Here, I propose a binocular information source for size perception. The model, drawing on the binocular geometry of viewing a physical extent, is expressed solely in terms of four angular measures and interocular distance, with the explicit exclusion of egocentric distance information. Thus, the proposed information source, if utilized by the binocular system, should be able to augment the few existing sources of information for size perception (e.g., familiar size, texture gradient, and horizon ratio).